(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study examines the impact of value-based training on promoting ethical organizational behavior within Libyan public administration institutions. It aims to analyze the role of value-based training in fostering ethical conduct among public employees by reviewing its theoretical foundations, exploring its relationship with ethical organizational behavior, and identifying the challenges that hinder its effective implementation within the Libyan administrative context. The study adopts a descriptive-analytical approach based on an extensive review of relevant academic literature, previous studies, and reports issued by oversight and accountability bodies concerning public sector performance and ethics. The findings indicate that value-based training constitutes a significant mechanism for enhancing integrity, professional commitment, accountability, and self-regulation among public employees. However, its integration into training programs implemented by Libyan public institutions remains limited and inadequate. The study further reveals an urgent need to incorporate value-based training into human resource development strategies and public-sector administrative reform initiatives. Accordingly, it recommends redesigning training plans and programs to emphasize public service values, linking them to institutional performance indicators, and embedding them within broader frameworks of public service ethics, value-based governance, and institutional integrity.